Stress, gender, and declension class in Belarusian - Bethin Christina Y. (Linguistics, 2022)
Ongoing innovations in Standard Belarusian nominal declension indicate that speakers are aware of and actively using paradigmatic stress patterns for grammatical purposes. The adoption of new mobile stress patterns in paradigms which originally had fixed stress is now complementary in Declension Ia masculine nouns and in Declension II feminine nouns; most neuter nouns simply default to fixed stem stress. The highlighting of grammatical gender distinctions via changes in paradigmatic stress patterns has led to a reanalysis of stress, gender, and declension class in common gender and a-stem masculine nouns and their case exponents have now become stress-dependent, a situation markedly distinct from that found in the other closely related East Slavic languages, Russian, and Ukrainian. These developments pose a challenge for several theories of morphology, either because the theory takes paradigmatic stress to be dependent on declension class or because the theory does not have a provision for paradigmatic stress to determine inflectional exponents.